CSC730 - Multimedia Design and Development / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2018)
This course introduces students to design and development of multimedia title. Hardware for development of multimedia product and for the playback is also discussed. This course also discusses about multimedia distribution and Delivery .